Microstructural evaluation of ball-milled nano Al2O3 particulate-reinforced aluminum matrix composite powders - Matori, Khamirul Amin; Mohamed Ariff, Azmah Hanim; Mohd. Yusoff, Hamdan; Yunus, Robiah; Ostovan, Farhad; Toozandehjani, Meysam; Oskoueian, Arshin (Carl Hanser Verlag GmbH & Co., 2015)
A mechanically alloyed mixture of Al-1 wt.% nano-alumina (n-Al2O3) composite powders was produced using a planetary ball milling machine. Different milling times were applied to investigate the effect of milling time on the dispersion and microstructure of n-Al2O3 particulate reinforcement within the aluminum matrix. A good homogeneous dispersion of n-Al2O3 particulates was observed after 8 h of milling. Longer milling times had no significant effect on the dispersion and morphology of n-Al2O3 particulates within the aluminum matrix because a steady state had been reached.